Tafsir Aḥkām of Qur'an Surah Al-Qaṣaṣ Verse 27 on Non-Material Mahr: An Academic Perspective - Fadhli, Muhajirul; Salman Abdul Muthalib; Nurjannah Ismail (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2026)
Qur'anic narratives are commonly interpreted as historical and moral accounts, often overlooking their normative and legal dimensions. Qur'an Surah Al-Qaṣaṣ verse 27, which presents service as a form of mahr (dower) in the marriage of Prophet Moses (Mūsā), has rarely been examined through the lens of Tafsir Aḥkām, particularly from the perspective of academics. This study aims to analyze the legal implications of the verse and explore academics' views on the legitimacy of non-material mahr and its relevance to contemporary marriage issues. Using a qualitative field approach, data were collected through in-depth interviews with nine academics specializing in Qur'anic Studies, Qur'anic Tafsir, Hadith, and Islamic law at UIN Ar-Raniry Banda Aceh, supported by documentary analysis of classical and contemporary tafsir and juristic literature. The findings reveal that the participants unanimously regard the verse as providing legal legitimacy for non-material mahr, provided it is mutually agreed upon, specified before the marriage contract, and beneficial. They also view service-based mahr as a potential solution to the growing burden of material mahr in Aceh, while emphasizing the need for cultural acceptance. The novelty of this study lies in integrating Tafsir Aḥkām with empirical evidence from academics' perspectives, demonstrating the relevance of Qur'anic narrative verses to the development of contemporary Islamic family law.